Desain Pembelajaran Trigonometri Menggunakan Model Pogil Untuk Siswa SMA - Siti Nuralif (Universitas Majalengka, 2023)
Learning mathematics in schools is intended so that students have mathematical abilities. Mathematical abilities are trained through mastery of mathematical material. Various alternative uses of learning models have been carried out in accordance with the development of science in education. So this study aims to provide alternative learning options, through the Trigonometry learning design using the POGIL model for high school students. POGIL is a process-oriented and student-centered inquiry learning in an active learning that uses study groups. This writing uses the Dick and Carey instructional design. The development of the Dick and Carey learning design model is a learning design model that follows a systematic approach to developing effective and efficient learning programs. Learning design is done by analyzing the needs of students. Performance objectives and learning outcomes are discussed in detail and adapted to instructional objectives. The results of this study indicate that the trigonometry learning design by applying the POGIL model is recommended for educators. This happens because learning is based on the advantages of the POGIL learning model, which include helping students to discover their own knowledge. In addition, the POGIL Learning Model is also able to assist students in improving process skills, asking questions, and communicating knowledge, and can cover a wide range of subject matter. The POGIL model is also easy to apply to all levels of education..Keywords: POGIL Model, Instructional Design, Trigonometry, High School Students